Attitudes of teachers and supervisors towards teaching prosody (Arūḍ) and rhyme within the Arabic language courses at the secondary level in the Kingdom of Saudi Arabia - Alowaydhi, Wafaa Hafize; Almutairi, Najla Marzuk (Journal of Educational and Psychological Sciences, 2020)
The study addressed the issue of teaching the science of prosody (Arūḍ) and rhyme in the secondary level with the aim of deciding to include it in the Arabic language courses at the secondary level, and to achieve the goal of the study the researchers used the descriptive survey method and designed an electronic questionnaire for the questionnaire of the study community consisting of all teachers and supervisors of the Arabic language For the secondary level and specialists teaching it in universities in Saudi Arabia and reached the participants in the referendum (430) and then the opinions were treated statistically using percentages and limited the percentage of supporters to teach it and opponents and the reasons of each team, and the result appeared in favor of supporters by 64.4% , and from The most important reasons for support is the role of performances and rhyme in the Arabic language calendar, and being a way to refine the talents of those who have poetic tendencies and open them the doors of interaction with the masterpieces of Arabic poetry and inspiring poetic music, and the percentage of opponents was 36.6% and their reasons were that the prosody (Arūḍ) and rhyme sacrilege is a science to which those who wish to specialize in the literary field in the university field and who have poetic tendencies and should not be circulated to all students.
Keywords: Teaching presentations and rhymes; Arabic courses; High school; Saudi Arabia